2013
DOI: 10.1179/1476830513y.0000000092
|View full text |Cite
|
Sign up to set email alerts
|

Damaging effects of a high-fat diet to the brain and cognition: A review of proposed mechanisms

Abstract: The prevalence of obesity is growing and now includes at least one-third of the adult population in the United States. As obesity and dementia rates reach epidemic proportions, an even greater interest in the effects of nutrition on the brain have become evident. This review discusses various mechanisms by which a high fat diet and/or obesity can alter the brain and cognition. It is well known that a poor diet and obesity can lead to certain disorders such as type II diabetes, metabolic syndrome, and heart dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
200
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(213 citation statements)
references
References 131 publications
(146 reference statements)
8
200
1
4
Order By: Relevance
“…This is in agreement with the report of Freeman et al (2014), who demontrated that a high fat diet could shorten the lifespan and accelerate the ageing. ROS, the most abundant free radicals in cells, are the byproducts of normal cellular metabolism of oxygen.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the report of Freeman et al (2014), who demontrated that a high fat diet could shorten the lifespan and accelerate the ageing. ROS, the most abundant free radicals in cells, are the byproducts of normal cellular metabolism of oxygen.…”
Section: Discussionsupporting
confidence: 93%
“…Adult epidemiological studies have also shown that intake of a high-fat diet that includes mostly n-6 and SFA is associated with worse performance on cognitive tasks (30) . These associations may be even more profound at early life, as the brain grows at its fastest rate during the first 3 years of life, and it is possible that poorer food choices during this early period may discourage optimal head and brain growth (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, reduced cognitive performance following consumption of a high fat (HF) diet has been observed in humans [7][8][9][10] and animals [11][12][13][14]. Mechanisms likely involved in diet-induced damage to the brain include impaired glucoregulation [15], increased oxidative stress, and increased inflammation in brain tissue [16][17][18][19]. Previous work from our laboratory provided evidence for impairment of cognitive function in rats fed a high fat high cholesterol (HFHC) diet, and suggested that alterations in the blood-brain barrier (BBB) and in microglial activation may contribute to the reduced spatial and working memory observed [12,20,21].…”
Section: Introductionmentioning
confidence: 98%